Analisa Pengaruh Media Pendingin Air Garam terhadap Kekerasan Hasil Kerajinan Pandai Besi - Ahmadin Ahmadin (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
Results blacksmith craft in South Sumatra, especially in the village of Tanjung Dayang, Limbang Jaya and Tanjung Pinang Ogan Ilir regency still less able to compete nationally and internationally. To overcome the above required touch on material technology that can improve the mechanical properties (hardness, wear resistance, tensile stress) and the corrosion results of a craft. Many methods can improve the mechanical properties of these metals is through the process of heat treatment, Nitriding process with quenching media are varied. In this study the authors will test the extent of the influence of the media quenching process cooling water, air and using water + salt (NaCl) to changes in material hardness. From the results of testing the chemical composition using SEM, the blacksmith craft test specimens are classified into medium carbon steel with a carbon content of 0.4%. Quenching process using the medium of the air conditioner of 88.7 HRB where, water + NaCl can increase the hardness of steel craft blacksmiths and maximum hardness that can be achieved by 24.7% (117.5 HRB) for specimen by quenching using water media + 10% salt. Quenching process using cooling media with ai r salt content of more than 10% (water + salt 10%) will occur fairly significant drop in violence from violence that is becoming 114.7 HRB.